Forensic and legal medicine in Chile: Cinderella without a prince - Leonardo González-Wilhelm; Mauricio Duce (Medwave)
Forensic medicine is of enormous importance in the functioning of contemporary justice systems worldwide. Therefore, in order to characterize the current state of medicolegal and forensic activity in Chile, a non-systematic review of the biomedical and legal literature on the subject was carried out. An analysis of open sources of information was also incorporated, including the National Registry of Individual Health Care Providers, the latest public accounts of the Forensic Medical Service, relevant background information available on the active transparency portal of that institution, exempt resolutions included in the “Chile Law” database (of the Department of Legislative and Documentary Services of the Library of the National Congress) and the lists of judicial experts appointed by the Courts of Appeals of the country for the biennium 2024 to 2025. We note that Chile maintains an unacceptable historical debt in terms of academic development and training of qualified professionals in forensic matters. Likewise, national scientific productivity in this field is practically null. Currently, forensic medicine is the medical specialty with the deepest shortage of professionals nationwide. Consequently, as in the early part of the last century, medical expert opinions are frequently performed by professionals untrained in forensic medicine. This scenario, taking into account the attitudes of certain lawyers and judges (detailed in the article), increases the risk of a miscarriage of justice. National public policies must take urgent action to address the deficits and provide solutions.